2011
DOI: 10.1515/cclm.2011.602
|View full text |Cite
|
Sign up to set email alerts
|

International Osteoporosis Foundation and International Federation of Clinical Chemistry and Laboratory Medicine Position on bone marker standards in osteoporosis

Abstract: The International Osteoporosis Foundation (IOF) and the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) Working Group on Bone Marker Standards (WG-BMS) has evaluated the clinical potential of bone turnover markers (BTMs) in the prediction of fracture risk and for monitoring treatment. Research evidence suggests that BTMs may provide information on fracture risk independently from BMD, so that fracture risk prediction might be enhanced by their inclusion in assessment algorithms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
232
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(246 citation statements)
references
References 33 publications
6
232
1
7
Order By: Relevance
“…The International Osteoporosis Foundation (IOF) and the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) recommended PINP and CTX-I as the reference BTMs in clinical studies [26,27]. From our perspective, PINP is a very robust bone marker, as among all the analyzed factors possibly affecting BTMs, only BMI influenced its values after excluding OCP use.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The International Osteoporosis Foundation (IOF) and the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) recommended PINP and CTX-I as the reference BTMs in clinical studies [26,27]. From our perspective, PINP is a very robust bone marker, as among all the analyzed factors possibly affecting BTMs, only BMI influenced its values after excluding OCP use.…”
Section: Discussionmentioning
confidence: 84%
“…Most studies were performed in premenopausal women but the age ranges were not identical, and contrary to Glover et al [18], we have found that women from 35 to 40 have as for CTX-I, and probably for other BTMs, may be different when assessing a broad age range in the premenopausal population. Our reference intervals, established in a narrow age range (35-45 years), may be particularly useful in the assessment of response to antiresorptive therapy in postmenopausal osteoporosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…These two markers were selected for the figure as they had the greatest magnitude of change and are also recommended as the reference bone markers by the IOF-IFCC Bone Marker Standards Working Group [9,28] .…”
Section: Responder Analysis -Premenopausal Meanmentioning
confidence: 99%
“…18 The International Osteoporosis Foundation (IOF) and International Federation of Clinical Chemistry (IFCC), IOF/IFF working group, have published recommendations to minimize variability in the determination of bone remodeling markers. 19,20 One bone resorption marker, serum CTX-I, and one bone formation marker, serum P1NP, are considered as reference markers and measured by standardized assays in observational and intervention studies. This, along with the consequent adoption of international reference standards, allows improving the use of these clinical markers.…”
Section: Laboratory Determination Of Biochemical Markers Of Bone Turnmentioning
confidence: 99%
“…11,29 Therefore, besides the calibration and the establishment of references for each laboratory, the ideal situation to control technical variability is to centralize the determinations in a unique laboratory. 20 ICTP ICTP, which reflects nonosteoclastic bone resorption mediated by MMPs, is liberated to the bloodstream during pathological conditions. Serum ICTP is quantified by RIA, 13 and it is relatively insensitive to changes in bone remodeling mediated by normal osteoclastic activity.…”
Section: Ctx-imentioning
confidence: 99%